PROPORSI ADAT BUDAYA DI BALI DAN PENGARUHNYA TERHADAP KESEJAHTERAAN MASYARAKAT LOKAL - Ni Putu Wiwin Setyari; I Komang Gde Bendesa; Ida Ayu Nyoman Saskara (Universitas Gadjah Mada, 2019)
A lot of the views of practitioners outside of Bali looked at the ceremony as one of the causes of poverty. It is seen from the portion of income that must be spent for various ceremonies to be performed by the Balinese Hindu community. This study aimed to answer the fundamental question, whether it is the customs and cultures led to affect Hindu community income in Bali? The data used is primary data from 350 Hindu households listed as poor households in Bali using depth interview survey method. Religion can play a role in overcoming poverty. Religion is not only a moral conscience that reminds the community will give generously to the poor but also to see the poor as human beings. The opinion says that the religious activities and custom made by Balinese Hindu communities causes increased poverty seems supported by the magnitude of the data portion of the expenditures for this activity. In Balinese Hindu communities, family income will be issued again and consumption expenditure shaped yajna. The analysis shows if traditional rituals and Balinese Hindu religious tend to have positive influence, good for people's income and the level of happiness. Therefore, it is not appropriate if the customs and religion are said to have made the Balinese Hindu community becomes poorer. This result also shows a shift in the understanding of religion in Balinese Hindu community. Religiosity someone then be interpreted by the implementation of the ritual in the form of upakara (yadnya) and the implementation of ethics in public life (susila).